2019
DOI: 10.1016/j.ijoa.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Management of postpartum haemorrhage: from research into practice, a narrative review of the literature and the Cardiff experience

Abstract: Postpartum haemorrhage (PPH) is caused by obstetric complications but may be exacerbated by haemostatic impairment. In a 10-year programme of research we have established that haemostatic impairment is uncommon in moderate PPH and that fibrinogen falls earlier than other coagulation factors. Laboratory Clauss fibrinogen and the point-of-care surrogate measure of fibrinogen (FIBTEM A5 measured on the ROTEM Ò machine) are predictive biomarkers for progression from early to severe PPH, the need for blood transfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 52 publications
(85 reference statements)
2
87
0
7
Order By: Relevance
“…There is some evidence that an escalating strategy for the management of increased bleeding after vaginal delivery can reduce postpartum haemorrhage rates , and this may also be applicable at caesarean section .…”
Section: Other Uterotonic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that an escalating strategy for the management of increased bleeding after vaginal delivery can reduce postpartum haemorrhage rates , and this may also be applicable at caesarean section .…”
Section: Other Uterotonic Agentsmentioning
confidence: 99%
“…The manufacturer states that carbetocin can be kept for 1 month at temperatures up to 60°C, 3 months at 50°C, 6 months at 40°C and 3 years at 30°C [82]. There is some evidence that an escalating strategy for the management of increased bleeding after vaginal delivery can reduce postpartum haemorrhage rates [92], and this may also be applicable at caesarean section [93].…”
Section: Carbetocinmentioning
confidence: 99%
“…study , there were significant reductions in red blood cell and plasma usage, obstetric haemorrhages with blood loss > 2500 ml, and critical care admissions across the whole population during the time of the study. When this study ended in November 2015, there was an increase in large haemorrhages similar to before the study and a local inquiry identified themes such as: the multidisciplinary team not attending the mother's bed‐side quickly; a return to estimating blood loss instead of the more accurate gravimetric assessment; viscoelastic haemostatic assays not being performed early; and delays in obstetric and haemostatic interventions . After these factors were rectified and guidance provided both on appropriate escalation during major obstetric haemorrhage and using ROTEM‐driven blood products within a specific pathway, outcomes improved to those found during the study by Collins et al.…”
Section: When Should Viscoelastic Haemostatic Assays Be Used During Omentioning
confidence: 93%
“…The correlation between Clauss fibrinogen and FIBTEM has an r 2 value of about 0.6, which demonstrates that they do not measure the same thing, but both have been found to be equally good at predicting progression to major obstetric haemorrhage . There is less evidence around viscoelastic haemostatic assay cut‐off values for the use of fresh frozen plasma where an EXTEM CT time of 75–100 s has been advocated . The poor prediction of PT and APTT for bleeding probably shows that this is a less important part of the algorithm, especially in obstetric practice, where generalised clotting abnormalities, which can be identified by significant derangements in the ROTEM‐EXTEM and TEG parameters, are a rare and late feature of major obstetric haemorrhage.…”
Section: Viscoelastic Haemostatic Assays For Obstetric Haemorrhagementioning
confidence: 99%
See 1 more Smart Citation